2020
DOI: 10.3390/ijms21113746
|View full text |Cite
|
Sign up to set email alerts
|

Differential Secretome Profiling of Human Osteoarthritic Synoviocytes Treated with Biotechnological Unsulfated and Marine Sulfated Chondroitins

Abstract: Symptomatic slow-acting drugs (SYSADOA) are increasingly used as effective therapies for osteoarthritis, representing an attractive alternative to analgesics or non-steroidal anti-inflammatory drugs to relieve disease symptoms. Pharmaceutical preparations of chondroitin sulfate, derived from animal sources, alone or in combination with glucosamine sulfate, are widely recognized for their beneficial effect on osteoarthritis treatment. A growing interest has also been devoted to understanding the molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…In fact, Stellavato et al 24 on primary human nasal chondrocytes and Russo et al 25 on knee joint synoviocytes and their collaborators reported about BC bioactivity on multiples biomarkers. Nevertheless, further studies are needed to unravel which is the main receptor/ligand through which BC exerts its action at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Stellavato et al 24 on primary human nasal chondrocytes and Russo et al 25 on knee joint synoviocytes and their collaborators reported about BC bioactivity on multiples biomarkers. Nevertheless, further studies are needed to unravel which is the main receptor/ligand through which BC exerts its action at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent secretome profiling showed similarities among CS and BC synoviocytes treatments, and indicated that BC had a more pronounced anti‐inflammatory activity. 25 Thus, considering the well‐explored effects of high molecular weight hyaluronan (H‐HA) 24 , 26 , 27 and BC features, the aim of this study was to investigate the properties of new hybrid complexes based on H‐HA together with BC (HHA/BC) compared with H‐HA and BC by themselves in an OA in vitro model based on human primary articular chondrocytes, as well as on primary synoviocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The current research is one of the first reports about BC (Russo et al, 2020) and hence the in-depth knowledge of its biochemical features, which are the main drivers toward bioactivity, are still under investigation. It can be argued that the unsulfated chondroitin is very similar to low MW, HA, differing in the immunostaining (green) on pellets treated as designated in the figure.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization comprised hydrodynamic and rheological analyses, which aimed to quantify and characterize the water-soluble HA included in the formulas and the viscosupplentation potential along with its variation due to dilution and HA-enzymatic hydrolysis (both phenomena occur in vivo after delivery). Moreover, we compared their bioactivity in a human primary cell model of OA, analyzing the cell morphology, viability and biosynthesis of key biomarkers of cartilage, and also evaluating specific mediators to address the inflammatory status [ 43 , 44 ]. To the best of our knowledge, this is the first study directly comparing both the biophysical and biochemical features of products for intrarticular injections based on the diverse chemical forms of hyaluronan.…”
Section: Introductionmentioning
confidence: 99%